Synthesis, Properties, and Two‐Dimensional Adsorption Characteristics of [6]Hexahelicene‐7‐carboxylic acid. Issue 41 (24th August 2016) - van der Meijden, Maarten W.; Balandina, Tatyana; Ivasenko, Oleksandr; De Feyter, Steven; Wurst, Klaus; Kellogg, Richard M.
Abstract: A convergent synthesis of racemic [6]hexahelicene‐7‐carboxylic acid by cross‐coupling of a bicyclic and a tricyclic component is described. A metal‐catalyzed ring‐closure is also a fundamental component of the synthetic approach. Scanning tunneling microscopy (STM) measurements of the racemate self‐assembled on Au(111) at liquid–solid interface revealed the formation of ordered racemic 2D crystals. Abstract : A winding road : A synthesis of 7‐carboxyhexahelicene1 has been developed using a convergent cross‐coupling synthesis that provides the 7‐methyl derivative in good yield. The methyl group proved to be remarkably recalcitrant to oxidation to the carboxylic acid of1 . Self‐assembly of1 from the liquid on solid Au(111) provided monolayers of well‐ordered racemic two‐dimensional crystals.